Quotas Operandi: Examining the Distribution of Voting Power at the IMF and World Bank. Issue 4 (2nd October 2017) - Clark, Rob
ABSTRACT: Existing work suggests that status hierarchies in the world polity are primarily realized through uneven participation rates in international organizations. Meanwhile, hierarchies that exist within these organizations remain neglected. I fill this gap by examining the unequal distribution of voting power at the International Monetary Fund (IMF) and the World Bank between 1951 and 2010. I first show that, while gross domestic product levels are converging between countries, votes at the IMF and World Bank are not. I then examine country-level factors associated with quota votes at the IMF and share votes at the World Bank. Net of the variables that comprise the official voting formulas, social networks tend to play a prominent role in how votes are allocated. Overall, these findings highlight the importance of examining power, material interests, and discretion within world polity institutions.